MODEL PEMBELAJARAN KOOPERATIF NHT MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PASSING BOLA BASKET - I Komang Aria Gunantara (Universitas Pendidikan Ganesha, 2013)
Abstrak: Penelitian ini bertujuan meningkatkan aktivitas dan hasil belajar passing bola basket melalui penerapan model pembelajaran kooperatif tipe NHT pada siswa kelas XI IA 1 SMA Laboratorium Undiksha Singaraja tahun pelajaran 2012/2013. Penelitian ini adalah penelitian tindakan kelas yang dilaksanakan dalam dua siklus, yang terdiri dari rencana tindakan, pelaksanaan tindakan, observasi atau evaluasi dan refleksi. Subjek penelitian adalah siswa kelas XI IA 1 SMA Laboratorium Undiksha Singaraja, berjumlah 39 orang dengan rincian 23 orang putri dan 16 orang putra. Data dianalisis menggunakan analisis statistik deskriptif. Hasil analisis data pada siklus I aktivitas belajar passing bola basket secara klasikal sebesar 7,42 (aktif), dan pada siklus II sebesar 9,16 (sangat aktif). Dari siklus I ke siklus II mengalami peningkatan sebesar 1,74. Persentase hasil belajar passing bola basket secara klasikal pada siklus I sebesar 74,36% (cukup baik), dan pada siklus II sebesar 94,87% (sangat baik). Dari siklus I ke siklus II mengalami peningkatan sebesar 20,51%. Berdasarkan hasil analisis data dan pembahasan disimpulkan bahwa aktivitas dan hasil belajar passing bola basket meningkat melalui penerapan model pembelajaran kooperatif tipe NHT pada siswa kelas XI IA 1 SMA Laboratorium Undiksha Singaraja tahun pelajaran 2012/2013. Abstract: This study aims at improving the learning activities and learning outcomes of basketball basic passing technique through the implementation of cooperative learning type NHT tho the students of class XI IA 1 SMA Laboratorium Undiksha Singaraja in academic year 2012/2013. This study is a classroom action research was conducted in two cycles. Each cycle consisted of planning, action, observation or evaluation, reflection. The subjects of this study were 39 students, which consisted of 23 females and 16 males. The data were analyzed by using descriptive statistics analysis. The result of data analysis in cycle I showed that the students activity in learning basketball basic passing technique classically was 7,42, which was considered as active. In cycle II, the students learning activity was 9,16, which was considered as very active. From those results, it can be stated that the students activity in learning basketball basic passing technique increased 1,74% in cycle II. The percentage of students learning outcome in learning basketball basic passing technique classically in cycle I was 74,36%, which was considered as adequately enough. While in cycle II, the percentage of the students learning outcome was 94,87%, which was considered as very good. Therefore, it can be stated that the students learning outcome in learning basketball basic passing technique increased 20,51% in cycle II. From the resultof the data analysis, it can be concluded that the implementation of cooperative learning type NHT improved the activity and learning outcome in learning basketball basic passing technique of the students of class XI IA 1 SMA Laboratorium Undiksha Singaraja in academic year 2012/2013.